Analysis of causes of Wastages of Construction Materials on Building Construction Site: Identifying causes and solutions for wastage of construction materials in the Indian construction industry (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Construction industry has been swiftly developing around the world from last three decade especially in India the rate of developing of this industry is very high. There is a lot of capital investment, is invested in this sector as well as this industry become second largest industry after agriculture in India in perspective of capital investment as well as employment generation. This industry directly related with GDP of nation. The bigger construction projects have been launched in power, infrastructure, building sector in recent year. The 60 to 70 expenditure of the any construction project spend on construction materials and it is found that huge quantity of wastage of material take place on site during the construction phase. Wastages of material has major problem in construction industry which must be recognize very efficiently. Effective control on wastages of material saves money, so that organizations profit margin will increase. More specifically, it has main impact on construction cost, construction productivity, time, environment aspect. At such circumstance reduction of wastage of material during the construction phase contribute major role in economy of that construction project. Impact on environment is also serious issue because due to wastages of material the natural resources which are used for production of that construction material also wasted. The majority of this wastage of material can be avoided by competent firm control over supervision of site, flow of construction material strict labour supervision. This paper identifies sources for wastages of construction material and critical factor causing wastages of material for those sources by using Delphi techniques and detailed questionnaires analysis.